Surface immobilization of Rhizopus oryzae (ATCC 96382) for enhanced production of lipase enzyme by multiple responses optimization - Potumarthi, R.; Liu, J.; Wan, H.; Danquah, Michael (John Wiley & Sons, Ltd, 2012)
A modified Response Surface Methodology was used for the optimization of lipase production by immobilized cells of Rhizopus oryzae (ATCC 96382). Multiple responses optimization strategy was adopted to optimize process condition of surface immobilization technique for the optimization of lipase productivity. Five parameters, pH, Temperature, revolutions per minute, olive oil and glucose were considered, and their effect was evaluated both qualitatively and quantitatively by using a modified central composite design approach and model validation. The second order regression equation was developed for the three yield parameters are Y P/B, Y L/P and Y L/B, where Y is the yield parameter at their corresponding values of L: Lipase (U/mL), P: Protein (mg/mL) and B: Biomass (mg/mL). The regression equation was fitted and model fit (R 2) was 0.604 (Y P/B), 0.746 (Y L/P) and 0.618 (Y L/B), respectively showing an effective fit. Further, the model was validated theoretically and experimentally at higher level of production. Different growth patterns were observed during 120 h of fermentation period.